Green service management at high technology service industry : a case study at AirAsia airline - Muhammad Azfar Abdullah (2018)
In the modern service industry, it is distinct that green services will be the next wave for the high technology service industry, to be truly environmental emphasized (which comply with the criteria of green competitive advantage). This research aims to generate new ideas in the knowledge domain of green services which has not been fully explored. To date, there is limited research area about green services in airlines industry and in any operations. Expanding from the hotel management, the researcher aims to explore the transformation of lean services principles to green services of an airline industry. Since an airline industry is a cross-border business, the compliance of global green and sustainability standards on air transport must strictly comply. The airline industry is the high technology service provider from gate to the gate which involves all the facilities in airport and airline and the services are provided along the journey from one destination to another destination. Two companies were selected: An airline operator, AirAsia (AA) as airline operator and Malaysia Airport Holding Berhad (MAHB) as airport operator. By using service management model integrating with the current green service practices applied; an interdisciplinary concept has been developed. This is important to comply with the case study research strategy in new knowledge generation, where the protocol constructed could be utilized academically and for industrial practically (locally and internationally). This research was grounded on social-constructionism under an exploratory study. The qualitative methods will be applied to this exploratory study. The qualitative case study approach was adopted through three data collection methods – interview, observation, and document analysis. A total of 30 managers and executives from AA and MAHB were chosen. The findings of this research indicated that the entire service process entails green practices from input process until output process. It was supported by the green human resources and green infrastructures in forming a green corporate image. Transportation service and policymakers can utilise the results of this study in their own scopes and process development. The application of the green service protocol in Malaysia particularly needs to be evaluated in the future to see how far it is impacting the whole service process.